PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI REDSTAR HOTEL JAKARTA - Rio Adi Pratama; Shinton Levi Siahaan (LPPM Universitas Asa Indonesia, 2017)
Purpose- The purpose of this study was to determine whether the work environment and work discipline affect the performance of employees in Redstar Hotel Jakarta. Design/methology/approach- Data were collected by using questionaire distributed to 100 respondents that use non probability sampling techniques were analyzed by using multiple linear regression analysis. Data were processed by using SPSS Windows version 2.0. Analysis technique used is multiple linear regression test, F test, t test, correlation coefficients and coefficients of determination. Findings- The results showed that working environment and working discipline have significantly effected on performance either partially and simultaneously Research limitations- Other variablke such as motivation and compensation were not included due to a certain difficulty.